1974
DOI: 10.1016/0094-5765(74)90066-6
|View full text |Cite
|
Sign up to set email alerts
|

The asymptotic structure of counterflow diffusion flames for large activation energies

Abstract: Abstract-The structure of steady state diffusion flames is investigated by analyzing the mixing and chemical reaction of two opposed jets of fuel and oxidizer as a particular example. An Arrhenius onestep irreversible reaction has been considered in the realistic limit of large activation energies. The entire range of Damkohler numbers, or ratio of characteristic diffusion and chemical times, has been covered. When the resulting maximum temperature is plotted in terms of the Damkohler number (which is inversel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
171
0
7

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 770 publications
(180 citation statements)
references
References 18 publications
2
171
0
7
Order By: Relevance
“…They play a significant role in flame attachment, lift-off, ignition and reignition processes of non-premixed systems. Many theoretical and experimental studies have been devoted to the structure and propagation of triple flames from various viewpoints [1][2][3][4][5][6][7][8]. However, fewer studies on NO X formation in triple flames have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…They play a significant role in flame attachment, lift-off, ignition and reignition processes of non-premixed systems. Many theoretical and experimental studies have been devoted to the structure and propagation of triple flames from various viewpoints [1][2][3][4][5][6][7][8]. However, fewer studies on NO X formation in triple flames have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The solution for the innermost scale follows the large activation energy asymptotic method (Liñán 1974;Fachini 1996;Fachini, Liñán & Williams 1999;Fachini 2005). Finally, typical results are presented and discussed in view of the model.…”
Section: Length Scales and Thermal Non-equilibriummentioning
confidence: 99%
“…The parameter m represents the ratio of the thermal flux downstream from the flame to the total heat release. Liñán (1974) proposed an approximate expression for a curve fit of the numerical solution of the problem in the reaction region, relating these two parameters by…”
Section: Outer Zone: Problem Of the Order Of Unitymentioning
confidence: 99%
“…For oxidizer-stream temperatures above T c , the ignited branch bifurcates from the frozen solution at a finite valué of the strain rate. The occurrence of ignition as a bifurcation as opposed to a smooth turning point as in conventional one-step asymptotic analyses [12] is a consequence of the autocatalytic character of the kinetic mechanism em-"An exception is a recent study by activation-energy asymptotics (S. R. Lee and C. K. Law, Combust. Sci.…”
Section: Introductionmentioning
confidence: 99%